Epilepsy-Related Outcomes in Children With Neonatal Cerebellar Injury. (May 2021) - Seese, Ronald R.; Cummings, Dana D.
Objective: Acute brain injury is a frequent perinatal neurologic complication that can involve the cerebellum. Although short-term outcomes of infants with neonatal cerebellar injury are well described, neurologic sequelae in older children are underreported. Here, we describe epilepsy-related outcomes in young children who suffered from neonatal cerebellar injuries. Methods: In-house automated software identified patients with neonatal brain injuries who were evaluated at our institution both as neonates (≤28 days) and as children (≥1 year). Neonatal hospital course, neuroimaging, and outcomes related to epilepsy were reviewed from the medical record. Patients were stratified into 2 groups based on neonatal brain injuries: those with cerebellar injury and those without cerebellar involvement. Results: Of the 282 neonates followed through childhood over the decade-long study period, 33 (12%) experienced neonatal brain injury. All 33 cases involved supratentorial injury, and 5 (15%) also included cerebellar injury. The development of epilepsy was significantly less likely in the group with cerebellar involvement (40%) compared to that with cerebellar sparing (82%; P = 0.043). In some cases, children with cerebellum-sparing injuries required admission for seizure control and developed drug-resistant epilepsy as well as status epilepticus. These outcomes occurred less frequently in the group with cerebellar involvement. Conclusions: Epilepsy-related sequelae may occur less frequently when the cerebellum is involved in neonatal brain injury. Larger prospective studies are needed to clarify how cerebellocortical networks impact functional brain connectivity and epilepsy longitudinally.